A QUALITATIVE STUDY ON THE USE OF SONG TO TEACH SPEAKING SKILL - Ririn Supiyati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This study aimed to describing the activities existed in the pre, whilst, post activity that were conducted and how the teacher assessed the students’ speaking ability in the class. The respondents of this study were the tenth grade students of SMA Islam Nusantara Malang in the academic year 2018-2019 and the English teacher. The data were analyzed in the form of descriptive qualitative analysis using data reduction, display data and drawing conclusion by narrating the information taken from observation checklist and field notes.Dealing with the implementation of using song to teach speaking skill, the findings of this study is executed. Including from pre-speaking activity, the teacher taught the students based on the lesson plan provided by the teacher and the students give a good respond for the teacher’s utterance. In whilst-speaking activity, teaching and learning speaking through songs run well due to the types of song has been prepare and appropriated based on the students’ level, even though there were several students could not sing the song with the good pronunciation. In post-speaking activity, the teacher gave the chance to the students to deliver their difficulties during the teaching and learning using song.  Almost all of students claimed that they had no difficulty in pronounce the words because they already knew the song in the previous meeting.The result of this study showed that teaching and learning speaking through songs helped the students to improve their vocabulary mastery and make them more excited in joining the speaking class. The use of song to teach speaking skill also helpful for the students’ pronunciation and make the students easier to practice speaking anytime they want. Keywords: song, speaking skill